OCA optical cement solution for folding screen protective film, protective film and preparation method
By optimizing the components and preparation process of OCA optical adhesive, the light transmittance and crease resistance of the folding screen protective film during repeated folding is solved, and a low-cost and high-performance OCA adhesive layer is achieved to meet the use requirements of the folding screen.
Patent Information
- Application Number
- CN202510746122.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2025-08-26
AI Technical Summary
The existing OCA optical glue for folding screen protective films has the problem of high cost and difficulty in maintaining high light transmission, no creases and no delamination during repeated folding.
OCA optical glue solution was prepared in a solvent system of toluene and ethyl acetate composite by isoocrylate, butyl acrylate, methyl acrylate, γ-acryloyloxypropyl trimethoxysilane and initiator to optimize the compatibility between polymeric monomers, form a product with uniform molecular chain structure, and combine epoxy curing agents and optimized curing processes to prepare an OCA glue layer with excellent fatigue resistance and light transmission.
The low-cost OCA adhesive layer has excellent peeling force, light transmittance and bending resistance to meet the needs of folding screens.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical adhesive technology, and in particular to an OCA optical adhesive liquid for a folding screen protective film, a protective film, and a preparation method. Background Art
[0002] The market for foldable screen devices is growing rapidly and increasingly popular. To prevent foldable displays from scratching or shattering during use, a protective film is required. This film typically consists of a hardened, wear-resistant surface layer, a base material, and an OCA adhesive layer. However, foldable screens must maintain high light transmittance, without creases or delamination, even after repeated folding (typically requiring over 200,000 bend tests). Therefore, OCA, as one of its core materials, must possess high light transmittance, ultra-high flexibility, and fatigue resistance to prevent cracking or delamination after repeated folding. Currently, the high-end OCA market is monopolized by foreign companies, resulting in high costs.
[0003] Therefore, it is necessary to improve the OCA optical adhesive used in the existing folding screen protective film and develop it in the direction of higher performance, lower cost and greater environmental protection. Summary of the Invention
[0004] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide an OCA optical adhesive for a folding screen protective film. The original adhesive is prepared by using isooctyl acrylate, butyl acrylate, methyl acrylate, acrylic acid, γ-acryloxypropyltrimethoxysilane and an initiator in a solvent system of toluene and ethyl acetate, optimizing the compatibility between the polymerized monomers to obtain a product with a uniform molecular chain structure. The OCA adhesive layer obtained after curing has excellent peel strength, light transmittance, adhesion and bending resistance; and the selection and compounding of raw materials reduce costs and are more economical.
[0005] To achieve the above technical effects, the technical solution of the present invention is: an OCA optical adhesive for a folding screen protective film, the OCA optical adhesive comprising an optical base adhesive, a curing agent, and a first solvent. The raw materials for preparing the base adhesive include, by mass, 270-283 parts of isooctyl acrylate, 50-62 parts of butyl acrylate, 318-330 parts of methyl acrylate, 40-55 parts of acrylic acid, 1-2 parts of γ-acryloxypropyltrimethoxysilane, 2.1-2.3 parts of an initiator, and 1250-1350 parts of a second solvent; The second solvent includes toluene and ethyl acetate.
[0006] A preferred technical solution is that the initiator is azobisisobutyronitrile.
[0007] The preferred technical solution is that the mass fraction of toluene and ethyl acetate is (4.1~4.7): (5.3~5.9).
[0008] The preferred technical solution is that, by weight, the OCA optical adhesive comprises 68-72 parts of optical base adhesive, 1.6-1.8 parts of curing agent and 26-30 parts of a first solvent, wherein the first solvent is ethyl acetate.
[0009] A preferred technical solution is that the curing agent is an epoxy curing agent.
[0010] The preferred technical solution is to divide the amount of toluene in the second solvent into a first portion of toluene, a second portion of toluene, a third portion of toluene, a fourth portion of toluene, and a fifth portion of toluene; divide the amount of ethyl acetate in the second solvent into a first portion of ethyl acetate and a second portion of ethyl acetate; and divide the initiator into a first portion of initiator, a second portion of initiator, a third portion of initiator, and a fourth portion of initiator; The preparation method of the original rubber comprises the following steps: S1': Dissolve γ-acryloxypropyltrimethoxysilane in butyl acrylate, then add isooctyl acrylate, methyl acrylate and acrylic acid and mix them all to obtain a polymerization monomer mixture; S2': mixing the first portion of toluene and the first portion of ethyl acetate into a reactor and heating to reflux; S3': Mix the polymerization monomer mixture and the first portion of initiator, add them dropwise into the reactor, and keep them warm for reaction; S4': adding dropwise the second portion of toluene and the second portion of the initiator mixture, the third portion of toluene and the third portion of the initiator mixture, and the fourth portion of toluene and the fourth portion of the initiator mixture in sequence, and carrying out heat-insulating reaction after the addition of the mixture; S5': After the reaction solution is cooled, a fifth portion of toluene and a second portion of ethyl acetate mixture are added.
[0011] The preferred technical solution is that in said S2', the temperature of heating to reflux is 85-90°C; In said S3', the polymerization monomer mixture and the first portion of the initiator are added dropwise for 2 to 2.5 hours, and the heat preservation reaction time is 2 to 2.5 hours; In the step S4', the time for sequentially adding the mixed solution dropwise is 12 to 18 minutes, and the mixed solution is kept warm for reaction for 1 to 1.5 hours after the dropwise addition; In the step S5', the reaction solution is cooled to below 50°C.
[0012] The preferred technical solution is that the mass ratio of the first portion of toluene, the second portion of toluene, the third portion of toluene, the fourth portion of toluene and the fifth portion of toluene is (8-9): (10.5-11.5): (12-13): (14.5-15.5): (9.5-10.5); The mass ratio of the first portion of ethyl acetate to the second portion of ethyl acetate is (58-60):(13-15); The mass ratio of the first initiator, the second initiator, the third initiator and the fourth initiator is (2-4): (9-11): (9-11): (21-23).
[0013] The second purpose of the present invention is to overcome the defects existing in the prior art and provide a protective film, including a substrate layer and an OCA adhesive layer, wherein the OCA adhesive layer is made by curing the above-mentioned folding screen protective film with OCA optical adhesive.
[0014] A third object of the present invention is to overcome the defects in the prior art and provide a method for preparing a protective film, comprising the following steps: S1: Prepare release film; S2: applying the above-mentioned OCA optical adhesive for the folding screen protective film on the surface of the release layer of the release film, and curing to obtain an OCA adhesive layer; S3: After the OCA adhesive layer is cured, a base material layer is laminated on its surface to obtain a protective film; The curing temperatures are set to 60±5°C, 80±5°C, 80±5°C, 100±5°C, 100±5°C, 110±5°C, and 80±5°C in sequence; The aging temperature is 43±5° C. and the aging time is 72±2 h.
[0015] The advantages and beneficial effects of the present invention are: The OCA optical adhesive for the folding screen protective film of the present invention is a raw adhesive prepared by using isooctyl acrylate, butyl acrylate, methyl acrylate, acrylic acid, γ-acryloxypropyltrimethoxysilane and an initiator in a solvent system of toluene and ethyl acetate. The compatibility between the polymerized monomers is optimized to obtain a product with a uniform molecular chain structure. The OCA adhesive layer obtained after curing has excellent peeling force, light transmittance, adhesion retention and bending resistance. The selection and compounding of raw materials are cost-optimized. DETAILED DESCRIPTION
[0016] The following examples are only used to illustrate the technical solution of the present invention more clearly, and are not intended to limit the scope of protection of the present invention.
[0017] Selection of polymerization monomers Isooctyl acrylate provides flexibility, low modulus and high viscosity; butyl acrylate balances flexibility and adhesion; methyl acrylate improves hardness, rigidity and cohesive strength; acrylic acid provides polar group carboxyl, enhancing adhesion and cross-linking sites.
[0018] Selection of curing agent The original adhesive contains carboxyl groups, and the epoxy curing agent used contains epoxy groups that react with the carboxyl groups without producing gaseous byproducts, making it suitable for thick coatings or large-area lamination. The cross-linked polymer obtained after curing contains stable ester and ether bonds, offering excellent heat resistance, acid and alkali resistance, and solvent resistance. The resulting OCA adhesive layer exhibits stronger adhesion to polar substrates (glass, ceramics, etc.). The epoxy ring-opening reaction minimizes volume shrinkage, reducing warping or delamination caused by internal stress. The epoxy system contains no residual -NCO groups, exhibits excellent long-term UV yellowing resistance, and has high transparency, making it suitable for optical applications (such as OCA adhesives).
[0019] Selection of γ-acryloxypropyltrimethoxysilane The double bond activity of acryloyloxy is low and the polymerization rate is slow, but the resulting polymer chain is more flexible (no methyl group restricts chain segment movement) and the transmittance is higher without the influence of methyl group.
[0020] Selection of initiator Azobisisobutyronitrile (AIBN) offers high reaction controllability, making it suitable for systems requiring slow, uniform polymerization to avoid sudden polymerization. The resulting polymer exhibits a narrow molecular weight distribution and stable free radical release, facilitating the formation of uniform polymer chains and improving the OCA's transmittance (>92%) and mechanical uniformity. It also facilitates the uniform dispersion of γ-acryloxypropyltrimethoxysilane within the polymer chain, enhancing its compatibility within the reaction system and the polymer's high-temperature resistance.
[0021] Choice of Second Solvent A mixture of toluene (non-polar) and ethyl acetate (polar) can synergistically dissolve reactants and copolymers of varying polarity, reducing the risk of phase separation during polymerization and improving solubility. As a non-polar solvent, toluene is highly compatible with the hydrophobic trimethoxysilyl moiety of silanes and effectively dissolves the compound. Ethyl acetate, being more polar than toluene, interacts with the acryloyloxy groups of silanes. This improves the dispersibility and compatibility of γ-acryloxypropyltrimethoxysilane in the reaction system, enhancing the polymer's dispersibility and the flexural resistance of the adhesive layer. Toluene, with its high chain transfer constant, allows for flexible molecular weight control by adjusting the mixing ratio, optimizing the modulus and elongation at break of the OCA.
[0022] Example 1
[0023] The OCA optical adhesive for foldable screen protective films comprises, by weight, 70 parts of base optical adhesive, 1.75 parts of curing agent, and 28.25 parts of a first solvent. The base adhesive is prepared from raw materials, by weight, including 280 parts of isooctyl acrylate, 60 parts of butyl acrylate, 320 parts of methyl acrylate, 40 parts of acrylic acid, 1.2 parts of γ-acryloxypropyltrimethoxysilane, 2.25 parts of initiator, and 1,300 parts of a second solvent. The first solvent is ethyl acetate, and the second solvent comprises toluene and ethyl acetate in a mass ratio of 0.44:0.56. The initiator is azobisisobutyronitrile. The curing agent is an epoxy curing agent (Shanghai Huayi Group Co., Ltd.).
[0024] Dividing the amount of toluene in the second solvent into a first portion of toluene, a second portion of toluene, a third portion of toluene, a fourth portion of toluene, and a fifth portion of toluene in a mass ratio of 8.5:11:12.5:15:10; The amount of ethyl acetate in the second solvent is divided into a first portion of ethyl acetate and a second portion of ethyl acetate in a mass ratio of 59:14; The initiator is divided into a first initiator, a second initiator, a third initiator and a fourth initiator in a mass ratio of 3:10:10:22; The preparation method of raw rubber comprises the following steps: S1': Dissolve γ-acryloxypropyltrimethoxysilane in butyl acrylate, then add isooctyl acrylate, methyl acrylate and acrylic acid and mix them all to obtain a polymerization monomer mixture; S2': the first portion of toluene and the first portion of ethyl acetate were mixed and put into the reactor, and heated to reflux at 87°C; S3': Mix the polymerization monomer mixture and the first portion of initiator, and add dropwise to the reactor for 2 hours. Keep the mixture warm for 2 hours. S4': the second portion of toluene and the second portion of the initiator mixture, the third portion of toluene and the third portion of the initiator mixture, and the fourth portion of toluene and the fourth portion of the initiator mixture are sequentially added dropwise, and the time for sequential addition of the mixtures is 16 minutes. After the addition of the mixtures, the mixtures are kept warm for 1 hour, that is, the second portion of toluene and the second portion of the initiator mixture are added dropwise over 16 minutes, and the reaction is kept warm for 1 hour; then the third portion of toluene and the third portion of the initiator mixture are added dropwise over 16 minutes, and the reaction is kept warm for 1 hour; then the fourth portion of toluene and the fourth portion of the initiator mixture are added dropwise over 16 minutes, and the reaction is kept warm for 1 hour; S5': Cool the reaction solution to below 50°C, and finally add the fifth portion of toluene and the second portion of ethyl acetate mixture to obtain a raw rubber with a solid content of 35%.
[0025] The protective film includes a substrate layer and an OCA adhesive layer, and the OCA adhesive layer is made by curing the above-mentioned folding screen protective film with OCA optical adhesive.
[0026] The preparation method of the protective film comprises the following steps: S1: Prepare release film; S2: applying the above-mentioned OCA optical adhesive for the folding screen protective film on the surface of the release layer of the release film and curing it to obtain an OCA adhesive layer. The curing temperatures are sequentially set to 60°C, 80°C, 80°C, 100°C, 100°C, 110°C, and 80°C. S3: After curing the OCA adhesive layer, a substrate layer is laminated on its surface to obtain a protective film. The curing temperature is 43°C and the time is 72 hours. The substrate layer includes a PET layer and a hardening layer. The surface of the PET layer away from the hardening layer is laminated with the OCA adhesive layer.
[0027] Among them, the thickness of the OCA adhesive layer (glass transition temperature at -31°C) is 25 microns, the release film is 50 microns, and the PET layer is 50 microns.
[0028] Example 2
[0029] Example 2 is based on Example 1, except that, in parts by mass, the raw materials for preparing the original rubber include 270 parts of isooctyl acrylate, 60 parts of butyl acrylate, 330 parts of methyl acrylate, 40 parts of acrylic acid, 1.2 parts of γ-acryloxypropyltrimethoxysilane, 2.25 parts of initiator and 1300 parts of the second solvent.
[0030] Example 3
[0031] Example 3 is based on Example 1, except that, in parts by mass, the raw materials for preparing the original rubber include 290 parts of isooctyl acrylate, 60 parts of butyl acrylate, 310 parts of methyl acrylate, 40 parts of acrylic acid, 1.2 parts of γ-acryloxypropyltrimethoxysilane, 2.25 parts of initiator and 1300 parts of the second solvent.
[0032] Example 4
[0033] Example 4 is based on Example 1, except that the second solvent comprises toluene and ethyl acetate in a mass ratio of 0.5:0.5.
[0034] Example 5
[0035] Example 5 is based on Example 1, except that the initiator is azobisisoheptanonitrile.
[0036] Example 6
[0037] Example 6 is based on Example 1, except that the amount of toluene in the second solvent is divided into a first portion of toluene, a second portion of toluene, a third portion of toluene, a fourth portion of toluene and a fifth portion of toluene in a mass ratio of 12:12:12:11:10.
[0038] Example 7
[0039] Example 7 is based on Example 1, except that the amount of toluene in the second solvent is divided into a first portion of toluene, a second portion of toluene, a third portion of toluene, and a fourth portion of toluene in a mass ratio of 8.5:16.5:22:10; The amount of ethyl acetate in the second solvent is divided into a first portion of ethyl acetate and a second portion of ethyl acetate in a mass ratio of 59:14; The initiator is divided into a first initiator, a second initiator, and a third initiator in a mass ratio of 3:20:22; The preparation method of raw rubber comprises the following steps: S1': Dissolve γ-acryloxypropyltrimethoxysilane in butyl acrylate, then add isooctyl acrylate, methyl acrylate and acrylic acid and mix them all to obtain a polymerization monomer mixture; S2': the first portion of toluene and the first portion of ethyl acetate were mixed and put into the reactor, and heated to reflux at 87°C; S3': Mix the polymerization monomer mixture and the first portion of initiator, and add dropwise to the reactor for 2 hours. Keep the mixture warm for 2 hours. S4': the second portion of toluene and the second portion of the initiator mixture, the third portion of toluene and the third portion of the initiator mixture are sequentially added dropwise, and the time for the sequential addition of the mixture is 16 minutes. After the addition of the mixture, the mixture is kept warm for 1 hour, that is, the second portion of toluene and the second portion of the initiator mixture are added dropwise over 16 minutes, and the temperature is kept warm for 1.5 hours; the third portion of toluene and the third portion of the initiator mixture are added dropwise over 16 minutes, and the temperature is kept warm for 1.5 hours; S5': Cool the reaction solution to below 50°C, and finally add the fourth portion of toluene and the second portion of ethyl acetate mixture to obtain the original rubber.
[0040] Example 8
[0041] Example 8 is based on Example 1, except that the amount of toluene in the second solvent is divided into a first portion of toluene, a second portion of toluene, and a third portion of toluene in a mass ratio of 8.5:3 to 8.5:10; The amount of ethyl acetate in the second solvent is divided into a first portion of ethyl acetate and a second portion of ethyl acetate in a mass ratio of 59:14; The initiator is divided into a first initiator and a second initiator in a mass ratio of 3:42; The preparation method of raw rubber comprises the following steps: S1': Dissolve γ-acryloxypropyltrimethoxysilane in butyl acrylate, then add isooctyl acrylate, methyl acrylate and acrylic acid and mix them all to obtain a polymerization monomer mixture; S2': the first portion of toluene and the first portion of ethyl acetate were mixed and put into the reactor, and heated to reflux at 87°C; S3': Mix the polymerization monomer mixture and the first portion of initiator, and add dropwise to the reactor for 2 hours. Keep the mixture warm for 2 hours. S4': add the second portion of toluene and the second portion of the initiator mixture dropwise over 30 minutes, and keep the reaction warm for 4 hours; S5': Cool the reaction solution to below 50°C, and finally add a third portion of toluene and a second portion of ethyl acetate mixture to obtain the original rubber.
[0042] Comparative Example 1 Comparative Example 1 is based on Example 1, except that, by weight, the raw materials for preparing the base rubber include 280 parts of isooctyl acrylate, 60 parts of butyl acrylate, 320 parts of methyl acrylate, 40 parts of acrylic acid, 2.25 parts of initiator, and 1300 parts of the second solvent. γ-acryloxypropyltrimethoxysilane is not included.
[0043] Comparative Example 2 Comparative Example 2 is based on Example 1, except that, in parts by mass, the raw materials for preparing the original rubber include 280 parts of isooctyl acrylate, 60 parts of butyl acrylate, 320 parts of methyl acrylate, 40 parts of acrylic acid, 1.2 parts of γ-methacryloxypropyltrimethoxysilane (KH-570), 2.25 parts of initiator and 1300 parts of the second solvent.
[0044] Comparative Example 3 Comparative Example 3 is based on Example 1, except that, in parts by mass, the raw materials for preparing the original rubber include 280 parts of isooctyl acrylate, 60 parts of butyl acrylate, 320 parts of methyl methacrylate, 40 parts of acrylic acid, 1.2 parts of γ-acryloxypropyltrimethoxysilane, 2.25 parts of initiator and 1300 parts of the second solvent.
[0045] Comparative Example 4 Comparative Example 4 is based on Example 1, except that the second solvent is only ethyl acetate.
[0046] Performance Testing 1. Transmittance and haze: measured using Ultra Scan PRO instrument.
[0047] 2. Bending resistance: Dynamic bending test: Remove the release layer, adhere the OCA adhesive layer to a 0.1mm thick flexible tempered film, and then fix it to the folding screen test prop. The bendability test is performed using the LW-102W folding screen bending life tester. The test temperature is 25°C, the bending radius R is 1.5mm, the bending angle is 180°, and it is bent 200,000 times. The protective film is observed for blistering, cracking, shedding, creases, etc. Static bending test: The OCA adhesive layer of the uncompounded substrate layer is attached to the release film and then cut into 160mm long * 40mm wide strips. Then, a 1N weight (100g) is fixed to the tail of the sample with high-temperature insulating tape. The sample is hung on a fixture with a radius of R = 1.5mm. The sample is placed in a 60℃ / 90% humidity storage test chamber for 240 hours. After cooling, the width of the crease at the tail is measured. According to the current industry situation, a sample with a measured width of more than 35mm without creases has good bending resistance.
[0048] 3. Peel strength test: According to GB / T 2792-1998 standard, 180° peel strength test, where the substrate is glass / PI (polyimide film).
[0049] 4. Adhesion: According to GB / T4851-2014 standard, cut the protective film into standard tape (25mm wide, 100mm long), attach it to the glass, align the upper end with the standard line, cut off the excess part at the lower end, press back and forth three times with a 2kg roller, and place it at 100℃ for 30 minutes. Hang the glass with the sample vertically on the test stand and keep it still. Hang a 1kg weight underneath. The time it takes for the protective film to fall represents the adhesion of the protective film.
[0050] The performance test results of the embodiments and comparative examples are as follows:
[0051] In Example 4, compared with Example 1, the increased toluene content affects the reflux temperature of the second solvent system. In the original temperature system, a stable system cannot be reached, which has a negative impact on the molecular weight of the polymer and the viscosity of the reaction system, easily leading to insufficient reaction of the reactants and a decrease in the flatness of the film surface during coating.
[0052] Compared with Example 1, the initiation rate of azobisisoheptanonitrile in the reaction system is fast, which is not conducive to controlling the reaction rate and has a negative impact on the performance of the product.
[0053] In Example 6, compared with Example 1, adding too much toluene in the early stage will affect the reflux temperature of the second solvent system. In the original temperature system, a stable system cannot be achieved, which has a negative impact on the molecular weight of the product and the viscosity of the reaction system, easily leading to insufficient reaction of the reactants and a decrease in the flatness of the film surface during coating.
[0054] Compared with Example 1, the setting of adding toluene and initiator in stages in Example 7 has better control over the molecular weight of the product, the uniformity of the molecular segment structure and the viscosity of the reaction system, and has better reaction stability.
[0055] In Example 8, a violent reaction was observed, and the monomers imploded.
[0056] Compared to Example 1, Comparative Examples 1 and 2 demonstrated superior adhesive layer performance when compounded with γ-acryloxypropyltrimethoxysilane and the polymerizable monomers in this system. The addition of γ-methacryloxypropyltrimethoxysilane improved the high-temperature resistance of the resulting adhesive layer, but the reaction rate was fast and difficult to control, resulting in increased adhesive layer hardness and reduced flexural resistance. The methyl group present in the silane negatively impacted the light transmittance of the adhesive layer.
[0057] In Comparative Example 3, compared with Example 1, methyl methacrylate is used instead of methyl acrylate. Methyl methacrylate has a high glass transition temperature, the cohesion of the resulting adhesive layer is increased, and the high temperature resistance and adhesion performance are good. Under the condition that the ratio of the polymerized monomers remains unchanged, the bending resistance of the resulting adhesive layer decreases.
[0058] When the second solvent is only ethyl acetate, the cost is high, and the solubility of γ-acryloxypropyltrimethoxysilane in ethyl acetate in the reaction system is low, which is easy to affect the performance of the reaction product.
[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An OCA optical adhesive for a folding screen protective film, characterized in that: The OCA optical adhesive comprises an optical base adhesive, a curing agent and a first solvent. The raw materials for preparing the base adhesive comprise, by weight, 270-283 parts of isooctyl acrylate, 50-62 parts of butyl acrylate, 318-330 parts of methyl acrylate, 40-55 parts of acrylic acid, 1-2 parts of γ-acryloxypropyltrimethoxysilane, 2.1-2.3 parts of an initiator and 1250-1350 parts of a second solvent. The second solvent includes toluene and ethyl acetate.
2. The OCA optical adhesive for folding screen protective film according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.
3. The OCA optical adhesive for folding screen protective film according to claim 1 or 2, characterized in that: The mass fractions of toluene and ethyl acetate are (4.1-4.7): (5.3-5.9).
4. The OCA optical adhesive for folding screen protective film according to claim 1, characterized in that: Calculated by mass, the OCA optical adhesive comprises 68-72 parts of optical base adhesive, 1.6-1.8 parts of curing agent and 26-30 parts of a first solvent, wherein the first solvent is ethyl acetate.
5. The OCA optical adhesive for folding screen protective film according to claim 1 or 4, characterized in that: The curing agent is an epoxy curing agent.
6. The OCA optical adhesive for folding screen protective film according to claim 1, characterized in that: The amount of toluene in the second solvent is divided into a first portion of toluene, a second portion of toluene, a third portion of toluene, a fourth portion of toluene and a fifth portion of toluene; the amount of ethyl acetate in the second solvent is divided into a first portion of ethyl acetate and a second portion of ethyl acetate; the initiator is divided into a first portion of initiator, a second portion of initiator, a third portion of initiator and a fourth portion of initiator; The preparation method of the original rubber comprises the following steps: S1': Dissolve γ-acryloxypropyltrimethoxysilane in butyl acrylate, then add isooctyl acrylate, methyl acrylate and acrylic acid and mix them all to obtain a polymerization monomer mixture; S2': mixing the first portion of toluene and the first portion of ethyl acetate into a reactor and heating to reflux; S3': Mix the polymerization monomer mixture and the first portion of initiator, add them dropwise into the reactor, and keep them warm for reaction; S4': adding dropwise the second portion of toluene and the second portion of the initiator mixture, the third portion of toluene and the third portion of the initiator mixture, and the fourth portion of toluene and the fourth portion of the initiator mixture in sequence, and carrying out heat-insulating reaction after the addition of the mixture; S5': After the reaction solution is cooled, a fifth portion of toluene and a second portion of ethyl acetate mixture are added.
7. The OCA optical adhesive for folding screen protective film according to claim 6, characterized in that: In said S2', the temperature of heating to reflux is 85-90°C; In said S3', the polymerization monomer mixture and the first portion of the initiator are added dropwise for 2 to 2.5 hours, and the heat preservation reaction time is 2 to 2.5 hours; In the step S4', the time for sequentially adding the mixed solution dropwise is 12 to 18 minutes, and the mixed solution is kept warm for reaction for 1 to 1.5 hours after the dropwise addition; In the step S5', the reaction solution is cooled to below 50°C.
8. The OCA optical adhesive for the folding screen protective film according to claim 6, characterized in that: The mass ratio of the first portion of toluene, the second portion of toluene, the third portion of toluene, the fourth portion of toluene and the fifth portion of toluene is (8-9): (10.5-11.5): (12-13): (14.5-15.5): (9.5-10.5); The mass ratio of the first portion of ethyl acetate to the second portion of ethyl acetate is (58-60):(13-15); The mass ratio of the first initiator, the second initiator, the third initiator and the fourth initiator is (2-4): (9-11): (9-11): (21-23).
9. A protective film, characterized in that: It comprises a substrate layer and an OCA adhesive layer, wherein the OCA adhesive layer is prepared by curing the OCA optical adhesive for the folding screen protective film according to any one of claims 1 to 8.
10. A method for preparing a protective film, characterized in that: The following steps are involved: S1: Prepare release film; S2: coating the OCA optical adhesive for a foldable screen protective film according to any one of claims 1 to 8 on the surface of the release layer of the release film, and curing the OCA adhesive layer; S3: After the OCA adhesive layer is cured, a base material layer is laminated on its surface to obtain a protective film; The curing temperatures are set to 60±5°C, 80±5°C, 80±5°C, 100±5°C, 100±5°C, 110±5°C, and 80±5°C in sequence; The aging temperature is 43±5° C. and the aging time is 72±2 h.
Citation Information
Cited By
UTG folding screen protector and preparation method thereof
CN122232279A
UTG folding screen protection sticker and preparation method thereof
CN122232279B